Jugar con el lenguaje : Técnicas de expresión oral y escritas - Sánchez Romo, Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2001)
In this article some Speaking and Writing Techniques are presented. They were practiced with a group of students from the C.E.S. Don Bosco, who have a course on this subject within their curriculum. As for the exercices they did during their lesson and successful application of the techniques they carried out during their teaching practice period with Primary School students, the scores have been regarded as very positive, so that the most suitable exercices have been chosen to be used at each level. The gives suggestions and examples may offer other teachers same useful advice concerning their use at school.